Influence of piston shape and injector geometry on combustion and emission characteristics of syngas in direct-injection spark-ignition engine. (August 2018) - Fiore, Matilde; Viggiano, Annarita; Fanelli, Emanuele; Braccio, Giacobbe; Magi, Vinicio
Abstract: This paper presents a numerical study of the influence of piston shape and injector geometry on combustion and emissions characteristics of a direct-injection spark-ignition engine fueled by syngas (50% by volume of hydrogen, 50% by volume of carbon monoxide) under low/medium load conditions. Three different piston cup geometries namely: High-clearance Combustion Cup (HCC), Low-clearance Combustion Cup (LCC) and Omega Combustion Cup (OCC) have been considered with a compression ratio of 14. An axial full-cone gas jet injector has been considered together with a hollow-cone gas jet injector with several included half-angles, i.e. 30°, 45°, 52.5° and 60°. Computational fluid dynamics modelling has been performed to simulate the combustion process. The results indicate that, in terms of performance, OCC shape is favorable, even if OCC generates relatively higher NOx than the other two configurations. A further analysis has been performed by simulating an engine with OCC piston shape and an included half-angle of injection of 30°, by varying the Start Of Injection (SOI). The results show that the flame propagation velocity reduces as the SOI advances, since the fuel distribution becomes more homogeneous approaching to a premixed case. However, the flame speed reduction is partially balanced by the disappearance of very lean regions thanks to fuel convection and diffusion.